"Nocardia asteroides Complex in Patient with Symptomatic Pulmonary Nocardiosis in a patient with bronchiectasis (6). isolate the organism was also investigated." - S Eshraghi; M Amin (Tehran University of Medical Sciences, 2001)
Pulmonary nocardiosis is an acute or suppurative chronic disease, caused by aerobic actinomycetes which usually originates from soil and compost. Since Nocardia species have been isolated from the soil of different regions of Iran, as well as different cases of nocardiosis, this study was undertaken to evaluate the role and frequency of Nocardia in pulmonary infections.The present investigation was planned to isolate Nocardia bacteria from immunocompromised patients who had been referred to Maseeh-e-Daneshvari University Hospital (Tehran). 142 patients with advanced symptomatic pulmonary disease were studied during a period of seven months. Of all the patients surveyed, 102 were tested both for their BAL (bronchoalveolar lavage) and sputum. For the rest of the patient's sputum samples were not accessible. From each sample, three thin smears were prepared for microscopic observations. The samples were cultured in Sabouraud dextrose agar and paraffin agar. Medical history of patients were also recorded in the certain questionnaire for further data analysis. Nocardia asteroides was isolated from only a patient suffering from Cushing's syndrome with bronchogenic carcinoma [Ectopic adrenocorticotrophic hormone (ACTH) syndrome]. Further in-vitro investigation for differentiation of the isolate was performed and confirmed that the organism that grew on primary media was Nocardia asteroides complex. Our results revealed that the normal concentration of NaOH (4%), which is routinely being used for identification of Mycobacteria species, could inhibit the growth of Nocardia. Therefore, decontamination procedure of the samples collected for isolation of Nocardia was preformed using 1% NaOH in this study.